Faktor-Faktor Penghambat Pembelajaran Seni Budaya (Musik) Kelas XI IPA 2 MAN 3 Padang - Anggun Pitaloca; Hengki Armez Hidayat (Journal on Education, 2023)
This study aims to find and describe the factors inhibiting the learning process of cultural arts (music) class XI IPA 2 at MAN 3 Padang City. This type of research is qualitative research with descriptive methods. The instrument of this research is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data in this study used primary data and secondary data. Data were collected through literature study, observation, interviews and documentation. The steps of analyzing data are data reduction, data presentation and conclusion drawing. The results showed that learning cultural arts (music) in class XI IPA 2 MAN 3 Padang City still experienced obstacles in the implementation of learning cultural arts (music). These obstacles consist of 2 factors, namely internal factors and external factors. Internal factors in this study include; attention, interest, motivation, and learning readiness. External factors in this study include; learning methods, learning media, and infrastructure that should be prepared by teachers or schools. The efforts that teachers can make to overcome obstacles are to attract students' attention by providing motivation to increase students' confidence and responsibility to take part in music learning. Meanwhile, to overcome the limitations of facilities and infrastructure, teachers find alternatives by instructing students to bring their own musical instruments.